Upaya Komunikasi Dakwah Tokoh Masyarakat Dalam Menghadapi Krisis Akhlak Remaja di Desa Purun Kecamatan Penukal Kabupaten PALI - Mira .; Kusnadi .; Anang walian (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
The moral crisis of adolescents is becoming an increasingly worrying social challenge in Purun Village, Penukal District, PALI Regency. Various forms of behavioral deviations, such as declining social etiquette, lack of discipline, and weakening religious awareness, are phenomena that require serious attention. This study aims to analyze the da'wah communication efforts undertaken by community leaders in addressing this moral crisis. The research approach used is descriptive qualitative, with data collection techniques including observation, in-depth interviews, and documentation. The results show that community leaders implement da'wah communication strategies through personal approaches, religious lectures, youth development, strengthening religious activities in mosques, and collaboration with village officials and educational institutions. This da'wah effort focuses on moral development, strengthening moral values, and increasing religious understanding among adolescents. However, several obstacles exist, such as low participation among some adolescents, the negative influence of social media, and lack of parental supervision. This study concludes that da'wah communication conducted by community leaders plays a crucial role in shaping character and improving adolescent behavior. However, more intensive collaboration between community leaders, families, schools, and village governments is needed to ensure optimal and sustainable development of adolescent morality